K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

27 tháng 10 2017

đề tke mà

27 tháng 10 2017

x2-xy+y2
=x2-2xy+y2+xy
=(x-y)2+xy

4 tháng 12 2017

a, = (x^2+10x+25)-y62 = (x+5)^2-y^2 = (x+5-y).(x+5+y)

b, = xy.(x-y)

c, = (x-y).(x+y)+5.(x-y) = (x-y).(x+y+5)

k mk nha

17 tháng 10 2018

a,\(3x^2-30x+75=3\left(x^2-10x+25\right)=3\left(x-5\right)^2\)

b, \(xy-x^2-x+y=x\left(y-x\right)+\left(y-x\right)=\left(y-x\right)\left(x+1\right)\)

c,\(x^2-7x-8=x^2-8x+x-8=x\left(x-8\right)+\left(x-8\right)=\left(x-8\right)\left(x+1\right)\)

17 tháng 10 2018

a) 3x2 - 30x + 75 = 3.(x2 - 10x + 25) = 3.(x2 - 2.5.x + 52) = 3.(x-5)2

b) xy - x2 - x + y = x.(y-x) + (y-x) = (y-x).(x+1)

c) x2 - 7x - 8 = x2 + x - 8x - 8 = x.(x+1) - 8.(x+1) = (x+1).(x-8)

a)\(\left(x^2+4-4x\right)\left(x^2+4+4x\right)\)

b)\(x\left(y+1\right)+\left(y+1\right)=\left(y+1\right)\left(x+1\right)\)

c)\(\left(x+y\right)^2-2\left(x+y\right)=\left(x+y\right)\left(x+y-2\right)\)

17 tháng 9 2015

b) xy+1+x+y = x(y+1)+1+y = (x+1).(y+1)

24 tháng 10 2020

\(x^3+\frac{1}{x^3}=x^3+\left(\frac{1}{x}\right)^3=\left(x+\frac{1}{x}\right)\left(x^2-x+\frac{1}{x^2}\right)\)( x khác 0 )

\(-x^3+9x^2-27x+27=-\left(x^3-9x^2+27x-27\right)=-\left(x-3\right)^3\)

\(\left(xy+1\right)^2-\left(x-y\right)^2=\left(xy+1-x+y\right)\left(xy+1+x-y\right)\)

24 tháng 11 2016

a) x+ xy - 5x - 5y

=x(x+y)-5(x+y)

=(x-5)(x+y)

b) x2 - y2 - 4x + 4

=(x2-4x+4)-y2

=(x-2)2-y2

=(x-2-y)(x-2+y)

27 tháng 8 2017

a) x2 + xy - 5x - 5y

= x ( x + y ) - 5 ( x + y )

= ( x + y ) ( x - 5 )

b) x2 - y2 - 4x + 4

= ( x2 - 4x + 4 ) - y2

= ( x - 2 )2 - y2

= ( x - 2 + y ) ( x - 2 - y )

16 tháng 7 2015

\(=x^4+2x^3y-2xy^3-y^3=x^4+3x^3y+3x^2y^2+xy^3-x^3y-3x^2y^2-3xy^3-y^4=x\left(x^3+3x^2y+3xy^2+y^3\right)-y\left(x^3+3x^2y+3xy^2+y^3\right)=\left(x-y\right)\left(x+y\right)^3\)

20 tháng 7 2018

x3-x2y-xy2+y2

=x(x2-xy-y2+y2)

=x(x2-xy)

=x2(x-y)

19 tháng 12 2020

\(x^2+y^2-x^2y^2+xy-x-y\)

\(=x^2-x^2y^2+y^2-y+xy-x\)

\(=x^2\left(1-y^2\right)+y\left(y-1\right)+x\left(y-1\right)\)

\(=x^2\left(1-y\right)\left(y+1\right)+y\left(y-1\right)+x\left(y-1\right)\)

\(=\left(y-1\right)\left[-x^2\left(y+1\right)+y-x\right]\)

\(=\left(y-1\right)\left[-x^2y-x^2+y-x\right]\)